Staged heart transplantation and chemotherapy as a treatment option in patients with severe cardiac light-chain amyloidosis - Kristen, Arnt; Sack, Falk-Udo; Schönland, Stefan; Hegenbart, Ute; Helmke, Burkhard Maria; Koch, Achim; Schnabel, Philipp Albert; Röcken, Christoph; Hardt, Stefan; Remppis, Bjoern-Andrew; Goldschmidt, Hartmut; Karck, Matthias; et al. (European journal of heart failure, 2009)
Aims The prognosis of advanced cardiac light-chain amyloidosis is poor. Heart transplantation might enable causative therapy and ultimately improve prognosis. Methods and results Nineteen patients with cardiac amyloidosis but no obvious involvement of other organs were scheduled for heart transplantation. Four to 6 months later, high-dose melphalan chemotherapy and autologous stem cell transplantation (HDM-ASCT) was planned in patients not in complete remission. Seven of nineteen patients died while waiting for heart transplantation. The remaining 12 patients (complete remission, n = 4) underwent surgery. Chemotherapy in patients not in complete remission consisted of HDM-ASCT (n = 5/12; subsequent complete remission, n = 2; partial remission, n = 3) or melphalan-prednisolone (partial remission, n = 1). Two of twelve patients were ineligible for any chemotherapy. Three of twelve patients died [423.5 (105-2131) days] from progressive disease, relapse, or sepsis. The 1- and 3-year survival rates were 83 and 83%, respectively, similar to those of patients undergoing heart transplantation for standard indications. Corresponding survival rates stratified by haematological response were 100 and 100% for complete remission (partial remission, 100 and 100%; progressive disease, 0 and 0%). Conclusion Heart transplantation in advanced cardiac amyloidosis is a promising approach to interrupting the vicious circle of ineligibility for potential curative chemotherapeutic treatment and extremely poor prognosis of cardiac amyloidosis without chemotherapy. Highly urgent heart transplantation combined with subsequent HDM-ASCT appears to offer a successful treatment option to improve the poor outcome of cardiac amyloidosis. However, it should be restricted to highly selected patients in specialized centres.